Understanding Precocious Puberty: When Childhood Ends Too Soon - Muliana, Atriska Citra; Putri, Imey Pinasty Harianto; Prasetya, Rangga Cahya; Indratama, I Nyoman Yudayana; Athalia, Ihza Namira; Shafitri, Shira Shalsabina; Mertasari, Baiq Merna; Josafat, Gantha Narendra; Ilmiah, Janiya Abdila; As Shiddiq, Muhammad Hilmy; Aulia, Rashieka Salma; Ajmala, Indana Eva (Jurnal Biologi Tropis, 2025)
Precocious puberty is an endocrine disorder characterized by the premature development of secondary sexual characteristics, defined as occurring before the age of 8 in girls and 9 in boys. This literature review aims to understand precocious puberty: when childhood ends too soon. The article was compiled using a literature review method. Data were obtained through a search of various scientific sources, including international and national journals, textbooks, and clinical guidelines from the Indonesian Pediatrician Association (IDAI). Central precocious puberty, most often idiopathic in girls but associated with underlying pathology in boys, is caused by premature activation of the hypothalamic-pituitary-gonadal axis, while the peripheral form is caused by excess sex steroid production independent of gonadotropin stimulation. Clinical manifestations include early breast development, testicular enlargement, rapid linear growth, acne, and the early appearance of pubic or axillary hair. Diagnosis relies on a combination of careful history taking, physical examination, hormonal testing, bone age assessment, and imaging studies such as pelvic ultrasound or cranial MRI when indicated. Management strategies vary based on etiology, with gonadotropin-releasing hormone (GnRH) agonists being the standard treatment for central precocious puberty, while surgical or medical therapy is used for peripheral causes. In conclusion, precocious puberty is a childhood health issue of increasing concern due to its increasing global incidence. This condition not only impacts accelerated bone maturation and potential short stature in adulthood, but also impacts the child's psychological well-being and causes emotional distress to the family.